Comparison of mechanical properties of a new fiber reinforced composite and bulk filling composites - Hazem Abouelleil; Nelly Pradelle; Cyril Villat; Nina Attik; Pierre Colon; Brigitte Grosgogeat (Korean Academy of Conservative Dentistry, 2015)
Objectives The aim of this study was to evaluate the mechanical and physical properties of a newly developed fiber reinforced dental composite. Materials and Methods Fiber reinforced composite EverX Posterior (EXP, GC EUROPE), and other commercially available bulk fill composites, including Filtek Bulk Fill (FB, 3M ESPE), SonicFill (SF, Kerr Corp.), SureFil (SDR, Dentsply), Venus Bulk Fill (VB, HerausKultzer), Tetric evoceram bulk fill (TECB, Ivoclar Vivadent), and Xtra Base (XB, Voco) were characterized. Composite samples light-cured with a LED device were evaluated in terms of flexural strength, flexural modulus (ISO 4049, n = 6), fracture toughness (n = 6), and Vickers hardness (0, 2, and 4 mm in depth at 24 hr, n = 5). The EXP samples and the fracture surface were observed under a scanning electron microscopy. Data were statistically analyzed using one-way ANOVA and unpaired t-test. Results EXP, FB, and VB had significantly higher fracture toughness value compared to all the other bulk composite types. SF, EXP, and XB were not statistically different, and had significantly higher flexural strength values compared to other tested composite materials. EXP had the highest flexural modulus, VB had the lowest values. Vickers hardness values revealed SF, EXP, TECB, and XB were not statistically different, and had significantly higher values compared to other tested composite materials. SEM observations show well dispersed fibers working as a reinforcing phase. Conclusions The addition of fibers to methacrylate-based matrix results in composites with either comparable or superior mechanical properties compared to the other bulk fill materials tested.